Les écrits des Poilus Miroir du français au début du XXe siècle - Carles, Hélène (ELiPhi, 2020)
This book offers a thorough and detailed analysis of the exemplary dictionary of the Mots des Poilus (The language of the "Poilus") by Pierre Rézeau (2018). On the basis of some 15,000 citations which illustrate the extensive nomenclature of the dictionary, the fourteen authors emphasise the linguistic diversity of a country which was still entirely plurilingual, shedding light on the variation displayed by French dialects, regional varieties, argot and literary writing. The book details the impact of the Great War on the history of written French through an analysis of the daily correspondence between soldiers and their families, which amounts to almost ten billion letters written over a period of four years. A new and sometimes unexpected portrait of the French diasystem at the beginning of the twentieth century emerges, revealing numerous lexical, grapho-phonetic and morphosyntactic particularities. The linguistic choices which frequently diverge from those found in contemporary correspondence written in Italian or German are described in a complementary section. The appendix contains texts which supplement the chronological description of the Mots des Poilus, and a detailed analysis of the letters written by the wife of a Breton soldier provides an overview of the grapho-phonetic and morphosyntactic characteristics typically found in the letters.